MANAJEMEN STRATEGIS KAMPUNG ZAKAT INOVATIF SEBAGAI PUSAT PEMBERDAYAAN MASYARAKAT DI KABUPATEN JEMBER - Sholikhah, Villatus (LAN TABUR : Jurnal Ekonomi Syariah, 2024)
The Indonesian Central Statistics Agency (BPS) states that many poor people live in villages. So that village community empowerment can be carried out optimally, several approaches have been taken by experts, including the implementation of strategic management-based community empowerment. The implementation of strategic management in the context of village community empowerment has been carried out well by Bangsalsari SDGs Village and Sumber Jambe Integrated Zakat Village, Kab. Jember. This research uses qualitative research methods with a multicase research type. The results of the research show, namely: 1) strategic planning for innovative zakat villages consisting of formulating a vision and mission, analyzing environmental conditions and SWOT analysis. These three things result in the formulation of strategies, namely: implementing and increasing cooperation; carrying out initial surveys in local communities; implementation of training for creativity, entrepreneurship and so on; providing counseling and teaching; and providing assistance; 2) strategic implementation of innovative zakat villages focused on poor people, orphans, old widows, the elderly and the unemployed. The implementation of the program includes the program that has been formulated. The implementation went well and effectively; and 3) Strategic evaluation of innovative zakat villages is carried out using evaluation of the process and results of implementing empowerment activities. Evaluation is carried out to measure the level of success in each empowerment activity that has been implemented as well as to serve as evaluation material for considerations for future empowerment activities. Keywords: Strategic Management, Innovative Zakat Village, Community Empowerment